PENGARUH HARGA, CITRA MEREK DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN ROKOK GUDANG GARAM SURYA 12 (STUDI PADA KONSUMEN DI KABUPATEN GRESIK) - Mohammad Mashudy; Moh Agung Surianto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The goal of this study was to determine the impact of price, brand image, and reference groups on Gudang Garam Surya 12 cigarette purchasing decisions in Gresik Regency. In this study's analysis, the following tests are used: the t test (partial), the F test (simultaneous), the normality test, the multicollinearity test, the heteroscedasticity test, the multiple linear regression test, and the determination coefficient test (R2). In this study, questionnaire instruments were used to collect accurate data from 100 customers who bought Gudang Garam Surya 12 cigarettes in Gresik. SPSS is a testing application. The findings of the partial t test research indicate that price, brand image, and reference groups all significantly influence consumers' decisions to buy. According to the findings of the (simultaneous) F test inquiry, the Price, Brand Image, and Reference Group components all have an impact on Purchasing Decisions.